Numerical simulation of three degrees of freedom ball joint crossed spherical gear for a robotic arm prosthesis (LACCEI, 2024)
The objective of this article was to evaluate through finite elements the design of a crossed spherical gear with two different materials (polyether ether ketone - PEEK and titanium alloy - Ti-6Al-4V) for a robotic arm prosthesis. ANSYS mechanical was used to simulate strains, stresses, natural frequencies and modes of vibration through the elements. The results obtained show that the maximum stresses are under the same edge conditions, therefore they are close between the two materials, however the titanium alloy material (Ti-6Al-4V) has a higher safety factor compared to PEEK. . Therefore, the spherical crossed gear made of titanium alloy base material has better dynamic behavior and a higher safety factor in the event of an eventual overload of the robotic arm prosthesis.